The Land of Fires. Evaluating a State Law to Restore the Narrative Power of Local Communities - Lucchini, Fabio; Membretti, Andrea (PARTECIPAZIONE E CONFLITTO, 2016)
This study proposes a public evaluation of the Law 6/2014, approved by Italian Parliament to counteract a longstanding waste emergency in the area known as Land of Fires, in the provinces of Naples and Caserta, Campania region. The authors intended to explore, together with its recipients and from a sociological perspective, a state law, its impact, and the complex and interactive link between health and popular mobilization. It is intended, therefore, to propose a concrete idea of evaluation that is not impose from above and managed by neutral evaluators (technical experts). Based on in-depth work field, the evaluation process described here is configured as a non-hierarchical participative act, realized through a methodology aimed at encouraging self-control practices, taking possession of their own context by subjects that are not evaluated but rather co-evaluator, within a space of negotiation that can also become a field of conflict, open to different interpretations